ReqGIS Classifier: a tool for geographic requirements normalization - Saldaño, Viviana E. (2011)
Component Based Software Development (CBSD) is a development process based on components’ reuse. One of the main difficulties for developers is selecting the most suitable component that fit in their development systems. In this paper we describe a software tool, named ReqGIS, which supports our methodology for improving components’ identification in a geographic information environment. In particular, we introduce a new component named AlgSim, which completes the automation of the whole methodology. It starts analyzing user requirements specified by use cases and returns the best fitting geographic service category corresponding to those requirements.